The Influence of Financial Literacy and Financial Behavior on Financial Well-being Moderated by Family Economic Education - Aliffansyah, Dhani; Sudarno; Sabandi, Muhammad (Universitas Negeri Semarang, 2024)
This study aims to (1) the effect of financial literacy on financial well-being of UNS students; (2) the effect of financial behavior on financial well-being of UNS students; (3) the effect of family economics education in strengthening financial literacy and financial behavior on financial well-being of UNS students. This research was quantitative research with a population of UNS students. This study used 269 samples by using probably sampling technique. The data collection technique was used a Likert scale of 1-5 points and a dummy variable which was distributed directly via the Google form. Test the validity of the instrument using Confirmatory Factor Analysis (CFA) and test the reliability using Cronbach Alpha. The research hypothesis was tested using Moderated Regression Analysis (MRA) after descriptive statistical tests and analysis prerequisite tests were carried out and processed with SPSS 24 software. This study gave the results that (1) there was a positive and significant effect of financial literacy on the financial well-being of UNS students; (2) there was a positive and significant influence of financial behavior on financial well-being of UNS students; (3) family economic education moderates the relationship between financial literacy and financial behavior on the financial well-being of UNS students.